Teacher Strategies in Teaching English Reading: Exploring Students’ Perceptions - Wanci, Amelia; Tahir, Saidna Zulfiqar B.; Hajar, Ibnu (Jadila: Journal of Development and Innovation in Language and Literature Education, 2026)
Reading comprehension is a fundamental component of English language learning; however, many English as a Foreign Language (EFL) students continue to experience difficulties in understanding English texts. The effectiveness of reading instruction is therefore closely related to the instructional strategies employed by teachers. This study aimed to investigate the instructional strategies implemented by an English teacher in teaching English reading at MTs Balpetu, South Buru Regency, and to explore students’ perceptions of these instructional practices. A qualitative descriptive research design was employed. Data were collected through classroom observations, semi-structured interviews with the English teacher and students, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings revealed that the teacher implemented four complementary instructional strategies: cognitive, social, psychomotor, and affective strategies, with cognitive strategy serving as the dominant instructional approach. Students generally perceived these instructional strategies positively because they enhanced reading comprehension, increased learning motivation, enriched vocabulary acquisition, promoted active classroom participation, and improved learning confidence. The study concludes that integrating multiple instructional strategies creates meaningful learning experiences that support students’ reading development in EFL classrooms. These findings provide practical insights for English teachers, particularly in rural secondary schools, regarding the implementation of student-centered instructional strategies that promote effective reading instruction.